Bankruptcy Prediction Analysis of PT Bukalapak.com Tbk Using Altman Z-Score and Springate S-Score Models for the 2022-2024 Period - Barri, Safiq Rofiul; Wardoyo, Catur Satriya (International Journal of Global Operations Research, 2025)
The rapid development of the digital technology industry in Indonesia has made e-commerce companies like PT Bukalapak Tbk face complex financial dynamics, including the potential risk of bankruptcy. This study aims to analyze and compare the potential bankruptcy of PT Bukalapak Tbk in the 2022–2024 period using two prediction models: the Altman Z-Score and the Springate S-Score. This study uses a quantitative approach with a descriptive-comparative method. The data used are secondary data in the form of PT Bukalapak Tbk's annual financial reports published on the Indonesia Stock Exchange and the company's official website. The analysis was conducted by calculating key financial ratios, which were then entered into the Altman and Springate formulas to obtain prediction scores. The calculation results show differences in trends between the two models. The Altman Z-Score model indicates that the company is in the gray zone to distress, indicating a potential risk of bankruptcy if financial structure improvements are not made. Meanwhile, the Springate S-Score model provides relatively more optimistic results with a tendency to be above the healthy threshold, although it still shows fluctuations in financial performance during the study period. These findings indicate that the sensitivity and focus of the variables used by each model influence the differences in prediction results. This research confirms that applying bankruptcy prediction models to digital technology companies requires considering the characteristics of industries with high operational costs but significant growth potential. The research findings are expected to contribute to company management, investors, and stakeholders in making strategic decisions based on financial risk analysis. Keywords: Bankruptcy, Altman Z-Score, Springate S-Score, Financial Analysis, PT Bukalapak Tbk